A Rare Case of Uterine Leiomyosarcoma with Metastasis to the Thyroid Gland - Gabriel Irizarry-Villafañe; Nadyeschka Rivera-Santana; Michelle Mangual-García; Alex González-Bóssolo; Rafael Trinidad-Hernández; Miosotis García-Maldonado; Víctor Carlo-Chévere (Case Reports in Endocrinology)
Uterine leiomyosarcomas are aggressive tumors associated with a poor prognosis. These neoplasms have high metastatic potential, more frequently affecting the lungs, liver, and peritoneum. There are very few cases of metastasis to the thyroid described in the literature. We present the case of a 47-year-old female diagnosed with uterine leiomyosarcoma metastatic to the thyroid gland. In this case report, we want to emphasize the utility of ancillary studies to help differentiate a leiomyosarcoma from anaplastic thyroid carcinoma since cytologic evaluation alone can be challenging.